Emerging drugs for the treatment of wound healing. (June 2015) - Zielins, Elizabeth R; Brett, Elizabeth A; Luan, Anna; Hu, Michael S; Walmsley, Graham G; Paik, Kevin; Senarath-Yapa, Kshemendra; Atashroo, David A; Wearda, Taylor; Lorenz, H Peter; Wan, Derrick C; Longaker, Michael T
<x xml:space="preserve">Abstract</x> Introduction: Wound healing can be characterized as underhealing, as in the setting of chronic wounds, or overhealing, occurring with hypertrophic scar formation after burn injury. Topical therapies targeting specific biochemical and molecular pathways represent a promising avenue for improving and, in some cases normalizing, the healing process. Areas covered: A brief overview of both normal and pathological wound healing has been provided, along with a review of the current clinical guidelines and treatment modalities for chronic wounds, burn wounds and scar formation. Next, the major avenues for wound healing drugs, along with drugs currently in development, are discussed. Finally, potential challenges to further drug development, and future research directions are discussed. Expert opinion: The large body of research concerning wound healing pathophysiology has provided multiple targets for topical therapies. Growth factor therapies with the ability to be targeted for localized release in the wound microenvironment are most promising, particularly when they modulate processes in the proliferative phase of wound healing.